Community Participation and Geographical Information Systems - Craig, William (CRC Press, 2009)
ave you ever considered how much effect information technology has on society throughout the world? Progress often places lower income and marginalized communities at a distinct disadvantage. Community Participation and Geographic Information Systems, however, offers a detailed look at numerous incidences around the world where communities have actually taken control of the technology and really used it to their advantage. This is presented in the form of case studies and models such as Philadelphia's neighborhoods, the Atlanta Project, and neighborhood revitalization in Minneapolis, reflect on public participation in GIS concepts, best practices, constraints and opportunities.